La formación del Archivo Nacional del Perú (1861-1920) - Guibovich Pérez, Pedro (Anuario de Historia de América Latina, 2025)
This article deals with the formation of the National Archive between 1861, the year it was created, until 1920, when it acquired full institutional autonomy and began to function as a public service. In this article I argue that the need to have a National Archive was based on two foundations. Firstly, to serve for the writing of national history, particularly of the colonial period; and, secondly, sustain the political interests of the State. However, six decades had to pass to achieve these goals. This was because he had to overcome economic difficulties and face the ups and downs of political history. To understand the need of a sector of the political and intellectual elite to have an archive, this article begins with a description of the state of the documentary heritage before 1861. It continues with the explanation of the circumstances of its legal creation and its length and eventful process of constitution as a service.
Keywords: National Archive of Peru; Peruvian Historiography; Manuel de Mendiburu; Peruvian Historical Archives.